Pendidikan Anak Usia Dini dalam Menanamkan Nilai Moderasi Beragama di Lingkungan Sekolah: Early Childhood Education in Instilling the Values ??of Religious Moderation in the School Environment - Muhammad Yusuf; Noor Baiti; Suci Lestari (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Early Childhood Education (PAUD) is a fundamental phase in character formation, including the development of moral, social, and national values. During this period, children begin to absorb the values of tolerance, justice, and respect for differences. Religious moderation is an important value to instill early so that students grow with an inclusive attitude and can live harmoniously in a diverse society. Objective: This study aims to analyze the role of PAUD institutions in instilling the value of religious moderation through learning, school culture, and social interactions. The research method used is a descriptive qualitative method. The subjects of this study were children and parents at ABA Kindergarten in Banjarmasin City. The approach used is a descriptive, qualitative method through observation of learning activities, interviews with teachers, and document analysis of RPPH and character-strengthening programs at the school. Data were analyzed through reduction, presentation, and conclusion drawing. The study found that PAUD plays a strategic role in instilling the value of religious moderation through guided play activities, habituating tolerant attitudes, and integrating this value into daily learning themes. Teachers are the main role models who implement fair attitudes, respect differences, and use inclusive language in daily interactions. Research has found that PAUD plays a strategic role in instilling the values of religious moderation through guided play activities, fostering a tolerant attitude, and integrating these values ??into daily learning themes.